Effectiveness of nanoscale zero-valent iron for the immobilization of Cu and/or Ni in water and soil samples - Gil Díaz, M. (2020)
In the last few years, the effectiveness of nanoscale zero-valent iron (nZVI) as a treatment for polluted waters and soils has been widely studied. However, little data are available on its efficacy for metal immobilization at low and moderate doses. In this study, the effectiveness of two doses of commercial nZVI (1 and 5%) to immobilize Cu and/or Ni in water and acidic soil samples was evaluated. The influence of the nanoremediation technology on iron availability, physico-chemical soil properties and soil phytotoxicity was also assessed. The results show that the effectiveness of nZVI to immobilize Cu and Ni in water and soil samples was determined by the dose of the nanomaterial and the presence of both metals. Nickel immobilization was significantly decreased by the presence of Cu but the opposite effect was not observed. nZVI showed better immobilization capacity in water than in soil samples. In water, the dose of 5% completely removed both metals, whereas at a lower dose (1%) the percentage of immobilized metal decreased, especially for Ni in Cu + Ni samples. In soil samples, 5% nZVI was more effective in immobilizing Ni than Cu, with a 54% and 21% reduction of leachability, respectively, in single contaminated samples. In Cu + Ni soil samples, nZVI treatment led to a significant decrease in Ni immobilization, similar to that observed in water samples. The application of nZVI induced a dose-dependent increase in available Fe—a relevant effect in the context of soil rehabilitation. Germination assays of Medicago sativa and Vicia sativa seeds revealed that treatment with nZVI did not induce phytotoxicity under the experimental conditions tested, and that the phytotoxicity induced by Ni decreased significantly after the treatment. Thus, the use of nZVI emerges as an interesting option for Cu and/or Ni immobilization in water samples. The effectiveness of nZVI to remove Cu from acidic soil samples was moderate, while for Ni it was strongly dependent on the presence of Cu. These observations therefore indicate that the results in water samples cannot be extrapolated to soil samples.